Impact of rural credit on the development of Brazilian agriculture - Nogueira, Ana Cristina Maria; Amaral, Ana Maria Santana; Andrade, Juliana Mafra Salgado; Avelar, Jefferson Soares; Góes, Bruno César [UNESP] (Centro Universitario de Maringa, 2023)
Rural credit is a type of financing aimed at individual producers, associations and cooperatives, and is intended to promote agricultural production. Through it, it is possible to make financial investments, expand operations and fund the production and sale of goods, and thus obtain greater profits. It is made available by public and private credit entities and its main objective is to contribute to the rural production development policy in the country. With the financing, producers get money to invest in technology, improving their infrastructure and increasing productivity. This article seeks to identify the role of rural credit in the economic growth of Brazil during the period 1974 to 2018, considering the importance of access to agricultural credit for the development of the rural sector.
Impacto do crédito rural no desenvolvimento da agricultura brasileira
Keywords: Agricultural Mechanization; Financing; Productivity; SNCR